High School to University in Ontario: Did an Extra Year Make a Difference? - Brady, Patrick; Allingham, Philip (Canadian Journal of Higher Education, 2005)
This study examined perceptions of preparedness for post-secondary education in the province of Ontario. Participants were 272 university students enrolled in the first year of a four-or five-year concurrent teacher education program and represented two distinctive groups: (a) entrants who had completed the old five-year Ontario Academic Credit system, and (b) those who were admitted to university via the new four-year program. They responded to a questionnaire which inquired into the degree to which they believed that their final year of secondary school had adequately prepared them for the transition to university level studies. Although data analysis did not reveal any significant difference between the two groups in terms of academic achievement, Grade 12s reported feeling less prepared overall for the challenges of university, especially in terms of the acquisition of specific academic skills, as well as adjustment to the university social milieu.